A new insight into the reaction behaviors of side-chain alkylation of toluene with methanol over CsX. Issue 13 (15th June 2018) - Li, Peidong; Han, Qiao; Zhang, Xiaomin; Yuan, Yangyang; Zhang, Yanfei; Guo, Hongchen; Xu, Li; Xu, Lei
Abstract : The crucial step for styrene production and the formation paths for the main side-products in the side-chain alkylation of toluene with methanol over CsX were unveiled. Abstract : Side-chain alkylation of toluene with methanol is a potential technology to realize the one-step production of styrene under mild conditions. Herein, a series of cesium X zeolites with different cesium contents were prepared through an ion-exchange method. The performance of the CsX zeolites was extensively investigated in the side-chain alkylation of toluene and methanol. The acid–base properties of the involved CsX were characterized and the results showed that the acid–base properties present regular changes with varied cesium contents. Based on the full understanding of the acid–base properties of the involved CsX, the reaction behaviors of the main and side reactions in the side-chain alkylation of toluene with methanol over CsX were investigated and new insights were revealed. It has been found that the crucial steps for the main reactions were the activation of toluene and the formation of formaldehyde from dehydrogenation of methanol when the cesium exchange degree of CsX was lower and higher than 32.3%, respectively. The hydride transfer reaction between styrene and carbon deposition is responsible for the formation of ethylbenzene over CsX with lower cesium contents, while the transfer hydrogenation of styrene with methanol and formaldehyde was the main path for ethylbenzene formation over CsX with higher cesium contents. And it was found that the existence of Brønsted acid sites accounts for the formation of xylene over CsX. These new findings will give a new insight into the reaction behaviors of the side-chain alkylation of toluene with methanol over CsX and may also provide a potential modification method for high-efficiency catalysts.